Biocellulose-based hydrogel dressing as a strategy for the management of chronic arterial wounds - de Moraes, Carolina Magro Barreiros [UNESP]; Bassanelli, Arthur Mestriner [UNESP]; Rodrigues, Lenize da Silva [UNESP]; Barud, Hernane da Silva; Fontes, Marina de Lima; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Castro, Meire Cristina Novelli E. [UNESP]; Bertanha, Matheus [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: To evaluate using a biocellulose-based hydrogel as an adjuvant in the healing process of arterial ulcers. Methods: A prospective single group quasi-experimental study was carried out with chronic lower limb arterial ulcer patients. These patients received biocellulose-based hydrogel dressings and outpatient guidance on dressing and periodic reassessments. The primary outcomes were the ulcer-healing rate and product safety, which were assessed by ulcer area measured in photographic records of pre-treatment and posttreatment after 7, 30, and 60 days. Secondary outcomes were related to clinical assessment by the quality-of-life scores (SF-36 and EQ-5D) and pain, evaluated by the visual analogue scale (VAS). Results: Seventeen participants were included, and one of them was excluded. Six patients (37%) had complete wound healing, and all patients had a significant reduction in the ulcer area during follow-up (233.6mm2 versus 2.7mm2) and reduction on the score PUSH 3.0 (p < 0.0001). The analysis of the SF-36 and EQ-5D questionnaires showed a statistically significant improvement in almost all parameters analyzed and with a reduction of pain assessed by the VAS. Conclusion: The biocellulose-based hydrogel was safe and showed a good perspective to promoting the necessary conditions to facilitate partial or complete healing of chronic arterial ulcers within a 60-day follow-up. Quality of life and pain were positively affected by the treatment.
Keywords: Atherosclerosis; Peripheral Arterial Disease; Wound Healing; Wounds and Injuries